Amyloid and tau PET in a middle‐aged, racially and ethnically diverse, community‐based cohort. (December 2021) - Lao, Patrick J.; Berroa, Joncarlos; Benavides, Andrea; Tejeda, Emely; Shouel, Heather; Igwe, Kay; Maas, Benjamin; Schupf, Nicole; Mayeux, Richard; Manly, Jennifer J.; Brickman, Adam M.
Abstract: Background: Alzheimer's disease (AD) pathophysiology (i.e., amyloid and tau) develops first and then leads to subsequent neurodegeneration and cognitive impairment. Anti‐amyloid or anti‐tau interventions would be most effective in the earliest stages of disease, prior to irreversible neuronal death, i.e., during midlife. Our objective was to characterize the patterns of distribution for amyloid and tau PET in a middle‐aged, racially and ethnically diverse sample. Method: In an ongoing study, participants (63±6 years old, 73% women, 19±5 years of education, 8 Non‐Hispanic White/21 Non‐Hispanic Black/47 Latinx) underwent amyloid PET imaging with Florbetaben (n=76; weighted average SUVR in Thaal phase regions) and tau PET imaging with MK‐6240 (n=59; average SUVR in Braak stages I‐VI) in the Offspring Study of Racial and Ethnic Disparities in Alzheimer's Disease. Amyloid positivity was considered at >1.25 global SUVR, while tau positivity was considered at >2SD above the mean in Braak stage I in an independent healthy sample. A series of general linear models on the region of interest and voxel level were performed to determine the associations among age, amyloid, and tau PET. Result: Regional patterns of amyloid and tau burden were similar across race/ethnicity groups (Figure 1). In our middle‐aged sample, 13% were amyloid positive, while 7% were tau positive in Braak stage I. Amyloid positivity was observed as early as 60 years old and tau positivity was observed as early as 62 years old. Older age was associated with increased global amyloid (r=0.36, p=0.001), but was not associated with tau burden in any Braak stage. Using amyloid continuously, increased global amyloid was associated with increased tau in Braak stage I (r=0.25, p=0.06), but not with tau in Braak stages II‐VI after adjusting for age. Using amyloid dichotomously, tau burden was higher in amyloid positive compared with amyloid negative individuals in Braak stages I‐V after adjusting for age (p<0.04; voxelwise results in Figure 2). Conclusion: Preliminary data suggest a range of AD pathophysiology during midlife in a racially and ethnically diverse sample. Amyloid increased in an age‐dependent manner, while tau increased in an amyloid‐dependent manner suggesting that the amyloid cascade begins in midlife.